Secondary or Concurrent Infections in Skin of Atopic Dogs - Joseph, Joice P; Patel, JS; Tank, PH; Barad, DB.; Thakre, BJ (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
In the present study, twenty atopic dogs were investigated for secondary skin infections using different diagnostic techniques. The majority of dogs were suffering from bacterial infections, especially Staphylococcal infection (90 %). Different commensals on skin like Staphylococcus spp., Aspergillus spp. (50 %), Malassezia spp. (45 %), Demodex spp. (25 %) etc. caused secondary or concurrent infections in many atopic dogs indicating the importance of atopy in recurrent or non-responding dermatitis with those commensal organisms.